PEMODELAN POLA ARUS DI KAWASAN PESISIR PANTAI KAWAL KABUPATEN BINTAN - Sarmada, Iqbal Faiz; Jaya, Yales Veva; Putra, Risandi Dwirama; Suhana, Mario Putra (Pusat Penelitian Sumberdaya Pesisir dan Laut, Universitas Maritim Raja Ali Haji, Indonesia, 2018)
Research on current pattern modeling has been carried out in the Kawal coastal area of Bintan Regency. Kawal Beach is a tourist area, settlement and anchorage for fishing boats. These conditions will have an impact on the sustainability of coastal activities and conditions such as abrasion, sedimentation and shoreline changes. The purpose of this study was to look at the movement patterns of currents generated by tides, winds and analyze the current phenomena that occur in the coastal area of the guard. This flow modeling is carried out for 5 days using software MIKE 21 by entering wind, tidal parameters as a current modeling generator force. Research results in getting currents in the coastal area of Kawal are classified as tidal currents. Current movement at high tide tends towards South-Southwest, while at low tide the movement pattern of the current leads to the North. Current conditions at the highest tide range between 0.6 - 1.80 m / s and relatively the same as current conditions when heading for the lowest ebb with a velocity value between 0.4 - 1.80 m / s.